Advances in High-Speed Microwave Photonic Signal Processing - R. A. Minasian
Photonic signal processing offers a new powerful paradigm for processing high speed signals, due to its inherent advantages of wide bandwidth and immunity to electromagnetic interference. Recently there has been a strong drive to realise photonic integrated circuits using Silicon Photonics. This paper describes recent advances in integrated microwave photonic signal processing and sensing. These include optical single sideband modulators that can remove the effects of dispersion in wideband microwave photonic links, optical vector network analysers with high resolution, broadband tunable filters, multi-function processors, and integrated photonic sensors using optical micro-ring resonators that demonstrate extremely high sensitivity. These microwave photonic processors provide new capabilities for the realisation of high-performance signal processing and sensing.
Keywords: Physics; Electronics; radiowave and microwave technology; direct energy conversion and storage